Mucoadhesive chitosan/OA nanoparticles charged with celecoxib inhibit prostaglandin E2 LPS‐induced in U937 cell line. Issue 37 (31st May 2017) - Méndez, Paula A.; Ortiz, Blanca L.; Vásquez, Gloria M.; López, Betty L.
ABSTRACT: The present study shows the potential of new carriers of celecocib (CEL) for prostaglandin E2 (PGE2) inhibition in U937 cell line. Self‐assembled nanoparticles based on oleic acid‐modified chitosan were covered with hyaluronic acid (HA) obtaining systems with spherical shape and particle size close to 300 nm. CEL was encapsulated and the encapsulation efficiency (%EE) was dependent of the drug solubility in acid media, reaching %EE of 75.5% and 58.2% to strong and weak acid, respectively. The covering with HA increased the mucoadhesive properties and, the cellular binding and cellular uptake in U937 cells. Nanoparticles prepared in strong acid presented zeta potential (ζ) of 43.8 ± 0.4 mV, which become toxic and stimulate the PGE2 production in U937 cells, at the concentration 1 mg/mL. However, nanoparticles prepared in weaker acid presented ζ of 36.5 ± 1.21 mV, showing nontoxic effect and inhibitory effect of PGE2 from 80.8 pg/mL until 43.4 pg/mL. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45288. Abstract :